Electroacupuncture-Related Metabolic Brain Connectivity in Neuropathic Pain due to Brachial Plexus Avulsion Injury in Rats - Hou, Ao-Lin; Zheng, Mou-Xiong; Hua, Xu-Yun; Huo, Bei-Bei; Shen, Jun; Xu, Jian-Guang (Frontiers in Neural Circuits, 2020)
OBJECT: This study aimed to investigate the analgesic effect of electroacupuncture (EA) in neuropathic pain due to brachial plexus avulsion injury (BPAI) and related changes in metabolic brain connectivity. METHODS: Neuropathic pain model due to BPAI was established in adult female Sprague-Dawley rats. Electroacupuncture (EA) stimulations (2/15 Hz, 30 min/day, 5-day intervention followed by 2-day rest in each week) were applied to the 5th-7th cervical “Jiaji” acupoints on the non-injured side for 11 weeks following BPAI (EA group, n=8). Three control groups included sham EA (non-electrical acupuncture applied to 3 mm lateral to the real “Jiaji” acupoints), BPAI-only and normal rats (no particular intervention) (8 rats in each group). Thermal withdrawal latency of the non-injured forepaw was regularly tested to evaluate the threshold of thermalgesia. Small animal [fluorine-18]-fluoro-2-deoxy-D-glucose (18F-FDG) PET scans of brain were conducted on days 28, 84 and 112 to explore metabolic alterations of the brain. RESULTS: In the EA group, the thermal withdrawal latency of the non-injured forepaw significantly decreased following BPAI and then increased following EA stimulation, compared with sham EA (P<0.001). Metabolic brain connectivities among somatosensory cortex (SC), motor cortex (MC), caudate putamen (Cpu) and dorsolateral thalamus (DLT) in bilateral hemispheres decreased throughout the 16 weeks' observation in the BPAI-only group, compared with the normal rats (p<0.05). In the EA group, the strength of connectivity among the above regions were found increased at the end of 4th week following BPAI, decreased at 12th week, and then increased again at 16th week (p<0.05). The changes of metabolic connectivity were uncharacteristic and dispersed in the sham EA group. CONCLUSION: The study revealed long-term and extensive changes of metabolic brain connectivity in EA treated neuropathic pain rats. Bilateral sensorimotor and pain-related brain regions were mainly involved in this process. It indicated that modulation of brain metabolic connectivity might be an important mechanism of analgesic effect in EA stimulation for the treatment of neuropathic pain.